THERAPEUTIC EFFICACY OF LUGOL’S IODINE AND AUTOLOGOUS PLASMA ALONG WITH HERBAL ECBOLICS IN COW WITH UTERINE INFECTION COWS - CHAVHAN, G U; SAWALE, A G; MARKANDEYA, N M; KUMAWAT, B L; PUPALWAD, S B (The Indian Journal of Animal Reproduction, 2023)
The present investigation was conducted to study the effect of intra uterine infusion of lugol’s iodine and autologous plasma along with the herbal ecbolic tablets on 72 animals. On basis of the pH, PMN cell count and White Side Test diagnosis of all cases were confirmed. All cases were categorized in Group-I, Group-II and Group-III. They were treated with 2 per cent lugol’s iodine in distilled water and autologous plasma @30ml, intrauterine route along with herbal ecbolic tablets orally in group-I and II, respectively. Group- III was kept as control. Before treatment it was observed that pH of Cervico vaginal mucus (CVM) was 8.12±0.06 and 8.13±0.07 which decreased after treatment to 7.37±0.06 and 7.55±0.08, while average of PMN cells were 8.91±0.37 and 9.70±0.41 as before treatment it and reduce to 4.66±0.44 and 5.20±0.64 in recovered cases in groups-I and II, respectively. Recovered cases were bred by AI or natural service. After follow up, recovery rate, conception rate and pregnancy rates were found as 75.00 per cent and 58.33 per cent, 77.27 per cent and 68.18 per cent, 59.04 per cent and 54.54 per cent from groups-I and II, respectively.